Modelos dinâmicos aplicados a sistemas de manufatura utilizando grafos de ligação: proposta de modificações - Maluf, Arthur Sarro (2020)
Companies compete in a fierce market, where the main focus is consumer satisfaction, forcing them to respond dynamically to market changes and instabilities. Due to these factors, more accurate, adaptable, robust and exploitable models are needed to represent these production systems. In this way, the present study analyzes dynamic models applied to manufacturing using the bond graph method. The aim is to present a detailed comparative analysis, discussing the variables used in the models, the mathematical equation and the context of their application. From the analysis of existing models, a model was taken as a basis. The chosen model uses a source of effort, represented by a minimum function, which introduces non-linearity and makes the design of controllers difficult. The effort variable has no physical meaning and becomes null due to the infinite capacities of the stocks, also making the transfer of power between the elements null, which is the main feature of the approach. The new equations for the model limit the capacities of the stocks, allowing the transfer of power between the elements and the use of the minimum function is not necessary. The systematic and extensive search carried out in the literature showed that models based on bond graphs with application in manufacturing are scarce. Thus, this work aims to contribute to the development of future works in this line of research. The manufacturing and operations management area benefits from this type of approach, which allows the use of control theory tools for dynamic analysis and for proposing prescriptive management guidelines from the simulation of closed-loop systems. In relation to other approaches used in the modeling of production systems, the bond graph approach stands out for its modularity, which allows the integration of different systems, subsystems and components. This, in turn, allows the representation of different configurations of production systems (e.g. flow shop, job shop).